2020
DOI: 10.3390/molecules25133096
|View full text |Cite
|
Sign up to set email alerts
|

A Nano Drug Delivery System Based on Angelica sinensis Polysaccharide for Combination of Chemotherapy and Immunotherapy

Abstract: Combination of chemotherapy and immunotherapy has been a promising strategy in cancer treatment. Polysaccharides from Angelica sinensis (AP), a well-known Chinese herbal medicine, have been proved to have good immunomodulatory activity. In the present study, an enzyme-sensitive tumor-targeting nano drug delivery system (AP-PP-DOX (doxorubicin), PP stood for peptide) was constructed. In this system, Angelica polysaccharides act as not only carriers to targeted delivery of drugs to tumor tissue but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…PF40 was negatively charged, and the zeta potential of PF40 was −31.61 mV. These results confirm that PF40 is a non-ionic polysaccharide [29,30].…”
Section: Zeta Potentialsupporting
confidence: 69%
“…PF40 was negatively charged, and the zeta potential of PF40 was −31.61 mV. These results confirm that PF40 is a non-ionic polysaccharide [29,30].…”
Section: Zeta Potentialsupporting
confidence: 69%
“…The study has shown that natural polysaccharides can activate T lymphocytes, B lymphocytes, macrophages and other immune cells to exert their immune activities (Chen & Huang, 2018 ). ASP could restore the balance of Th1/Th2 immune response, improve tumor microenvironment immunosuppression and enhance antitumor immune function, resulting in synergistic antitumor effect with DOX (Wang et al., 2020 ). Astragalus polysaccharides (APS) could exert anti-tumor effects by restoring immune organs, regulating cellular immune response and increasing the levels of cytokines IL-2, TNF-α and IFN-γ.…”
Section: The Effect Of Natural Active Ingredients Combined With Chemo...mentioning
confidence: 99%
“…They can be used as natural drug carrier for nano-drug delivery, which can improve the bioavailability and efficacy of drugs. At present, ASP (Wang et al., 2020 ), bletilla polysaccharide (Wang et al., 2019a ), Ganoderma lucidum polysaccharide (Zheng et al., 2021a ), ursodeoxycholic acid (MDCA) (Anwar et al., 2018 ), Semen Armeniacae Amarum protein (Lin et al., 2020 ) have been successfully used for the delivery of DOX, MTX, sulfasalazine and PTX. A summary of the studies of natural active components as drug carriers in NDCDS is shown in Table 3 .…”
Section: Advantages Of Ndcds Of Natural Drug Active Ingredients and C...mentioning
confidence: 99%
“…Many well‐designed new tumor immunotherapy strategies, for example, angelica sinensis increased the expression of IL‐2 and decreased the expression of IL‐10, which have improved survival rates in cancer therapy. [ 122 ] The combination of immunotherapy and improvement of TME provides an effective and safe synergistic strategy for the intervention of tumors. The microenvironments of enzymes play crucial roles in evading immune surveillance and offer favorable conditions for the progression of malignant cancers.…”
Section: Endo‐stimuli‐responsive Nanoparticles (En‐srnps) For Control...mentioning
confidence: 99%